An Improved Orthogonal Frequency Division Multiplexing System-Based Image Steganography Technique - Ali Y. Jaber; Ammar Al-Khafaji; Ahmed Mahfodh Mkhelf (Tikrit Journal of Engineering Sciences)
OFDM technology is one of the most promising digital modulation methods to achieve the highest data transmission rates in all communication systems. However, the CFO problem constitutes one of the obstacles in-building wireless communication systems, as it leads to the ICI problem, especially in OFDM systems. Moreover, CFO causes orthogonal loss between the sub-carriers in the case of divergent sub-carriers. In addition, the ICI causes a frequency mismatch in the transmitting and receiving stages. In this paper, the effect of the CFO on the performance of the OFDM system is analyzed by suggesting a CFO compensation method to reduce the ICI that occurs in OFDM systems. In the case of an additive white Gaussian noise channel, the computer simulation results demonstrated that the CFO was reduced by approximately 5.2 dB and 7.15 dB in QPSK and 64QAM, respectively, compared to the original variance method. In this context, a coding method was proposed to hide secret data in an image before the OFDM generation process based on the Least Significant Bit (LSB1 &LSB2) technology. Then, the data was extracted from the image upon receipt. Several methods can be used to estimate CFO to compensate for that change in OFDM, including measuring the error rate (BER) as an indicator of the effect of ICI. Moreover, the transmitted signal will be of high quality due to the ICI reduction, leading to channel normalization and reducing the receiving complexity.